2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--31969
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of the Effects of Pre-College Preparation and Use of Supplemental Instruction during the First Year on GPA and Retention for Women in Engineering

Abstract: is a fourth year undergraduate student at Northeastern University, majoring in chemical engineering and minoring in biochemical engineering. He has been involved in the Connections Chemistry Review program for three years. He has also held an undergraduate research position in a biomaterials laboratory on campus. He has completed two coops in the biotech industry, and is currently completing his third coop at a tissue engineering research laboratory at the University of Hannover in Germany. Ms. Caroline Ghio, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…The recent study of O’Dea et al involved 1.6 million students worldwide and found that female STEM students had significantly higher grades (3.1%) in their first year of the study than their male peers and that grades among female students were more consistent, but there were fewer top-scoring female students. Further, female students had higher five-year graduation rates and higher mean cGPAs (cumulative GPAs) at graduation compared with male students . According to social cognitive theory, role modeling has a significant impact on self-efficacy and gender development .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent study of O’Dea et al involved 1.6 million students worldwide and found that female STEM students had significantly higher grades (3.1%) in their first year of the study than their male peers and that grades among female students were more consistent, but there were fewer top-scoring female students. Further, female students had higher five-year graduation rates and higher mean cGPAs (cumulative GPAs) at graduation compared with male students . According to social cognitive theory, role modeling has a significant impact on self-efficacy and gender development .…”
Section: Introductionmentioning
confidence: 99%
“…Further, female students had higher five-year graduation rates and higher mean cGPAs (cumulative GPAs) at graduation compared with male students. 13 According to social cognitive theory, role modeling has a significant impact on self-efficacy and gender development. 14 Various studies have examined the correlation between courses taught by female faculty role models and student outcomes in maledominated science and engineering fields and have discovered that female instructors have a significant positive effect on female student grade performance, and less so on male students.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We previously have found that engineering students who accumulate a greater number of pre-matriculation credits generally achieve a higher GPA and are more likely to persist in a rigorous engineering environment. Conversely, students with fewer incoming credits tend to have lower retention and graduation rates [7].…”
Section: Consequences Of Preparedness For First-year Engineering Studiesmentioning
confidence: 99%
“…SI usage in the first year of an undergraduate engineering program can be an important indicator in predicting student academic achievement [2,7]. Self-efficacy is an attribute that could affect a student's willingness to utilize SI and is defined by Bandura as an individual's belief that they can successfully complete an endeavor [15].…”
Section: Self-efficacy Seeking Si and The Importance Of External Supp...mentioning
confidence: 99%
See 1 more Smart Citation